The Impact of the Anti-Predatory Lending Laws on Mortgage Volume - CHOI, Hyun Soo (Institutional Knowledge at Singapore Management University, 2012)
In this paper, I test the hypothesis that anti-predatory lending laws inhibited the volume of mortgage lending during the housing-bubble period. I use cross-state variation in the strictness of these laws and their application only to mortgage refinancing as opposed to home purchases to develop a difference-in-difference estimate of the impact of these laws on mortgage volume. Consistent with my hypothesis, I find that states with stricter laws had lower mortgage refinancing volume but exhibited no difference in home purchase mortgage volume. I also test whether by restricting mortgage refinancing, these laws impacted household expenditures and find that the laws reduced household expenditures.